Students’ Attitude to the Cynical Words Used by the Teacher in the Classroom - Ade Sarkosih; Duduh Abdulah (PROJECT (Professional Journal of English Education), 2018)
In the second language classroom, the teacher sometimes reminds or rebuke the students’ mistake by using the cynical word. This word is considered inappropriate because it tends to disparage the students. Thus it can hurt their feeling. This study is aimed to investigate the students’ attitude toward the cynical words used by the teacher in the classroom interaction. The method used was qualitative. The respondents were students at one vocational school in Batujajar, Bandung. The interview was used as the instrument to collect the data. The question of the interview was developed based on the component of attitude proposed by (Schiffman & Kanuk, 2004). The result showed that the students had a positive attitude toward the cynical words used by the teacher in the classroom. They thought it was quite effective to remind them of their mistake. Unfortunately, it had a negative impact on the students feeling. The students felt sad and embarrassed when the teacher rebuke them in front of their classmate. This indicates the teacher cannot use cynical words too often in the classroom interaction. It is better for them to use the other way that is more appropriate in reminding the students’ mistake.Keywords: attitude, cynical words, classroom interaction